Effect of salicylic acid on carotenoid content and shoot growth of Mas Cotek (Ficus deltoidea jack Var. Trengganuensis) plant - Azrina binti Ismail
Previous studies have revealed that Mas Cotek plant (Ficus de Ito idea Jack) has medicinal and pharmacological properties such as antioxidants, anti-inflammatory, anti-bacterial, and many more. Therefore, many studies have been conducted to analyze the bioactive compounds found in Ficus deltoidea (Fd) plant. However, the study of salicylic acid effect as plant elicitors to increase the bioactive contents and also to stimulate the growth of Fd plants are still limited. Carotenoids are beneficial bioactive compounds for the eyes and skin and have good antioxidant properties for human health. Therefore, this study is significant to see how salicylic acid can affect the carotenoid content as well as the shoots growth of seedlings Fd Jack var. trengganuensis. Specifically, this study has three objectives, first, to analyze the carotenoid content and to calculate the Retinol Activity Equivalent (RAE) in seven variteties of F. deltoidea leaves, second, to investigate the effect of salicylic acid on carotenoid content of Fd Jack var. trengganuensis young leaves and, third, to study the effect of salicylic acid on the shoots growth of Fd var. trengganuensis seedlings. Carotenoids from Fd leaves was extracted using acetone methanol solvent (7:3,v:v) and profiled using the instrument High Performance Liquid Chromatography (HPLC). Salicylic acid treatment on Fd var. trengganuensis seedlings was done for 30 days every 2 days interval by spraying those plants with different concentration of salicylic acid (0.00, 0.01, 0.1 and 1.00 milimolar (mM). Subsequenty, carotenoid content, retinol acivity equivalents (RAE) and shoots growth of Fd were calculated and recorded. The findings showed that first, from seven varieties of F. deltoidea leaves, the highest amount of carotenoid content of beta carotene was showed in Fd var. angustifolia while the lowest was showed in var. deltoidea. Meanwhile, the highest amount of carotenoid content of lutein was showed in Fd Jack var. trengganuuensis (159.75c Ilg/~,d) while the lowest amount of lutein was showed in var. deltoidea (23.003 ug/ul). For retinol activity equivalent (RAE) result showed that the highest amount of RAE amongst seven varieties of Fd was recorded by Fd Jack var. angustifolia (134.34d ug RAE) while the lowest amount of RAE was showed by var. deltoidea (1.193 Ilg RAE). Second, the results showed the highest amount of beta carotene was recorded in Fd leaves when it was treated with 0.10 mM concentration of salicylic acid, showed the increment about 151 % (282.00b ug/ul), meanwhile, using concentration 1.00 mM of SA showed decrease about 44% (63.003 Ilg/Ill) from control (0 mM). Besides that, lutein content at concentration of 0.10 mM of SA showed increament about 192% while at concentration 1.00 mM of SA showed decrease about 5.5% from control. Third, the highest percentage number of shoots after treated with salicylic acid was shown in Fd Jack var. trengganuensis seedlings treated with the 0.00 mM (control) of salicylic acid about (40.00b %) while the lowest percentage number of shoots produced was recorded by 0.10 mM concentration of salicylic acid about (6.003 %). In F. deltoidea leaves, there were two types of carotenoid such as lutein and beta carotene and also retinol activity equivalent (RAE). This study has shown that salicylic acid positively affect the carotenoid content and negatively affect the shoots growth of seedlings of Fd var. trengganuensis.